Pengaruh Pembelajaran Ethno-Deep Learning terhadap Literasi Budaya Siswa - Baiq Zulfah Purni Sari Ningrum; Agus Muliadi; Laras Firdaus; Sri Nopita Primawati (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Enhancing students' cultural literacy is crucial amidst the currents of globalization that are causing shifts in local cultural values. Conventional teaching methods are considered inadequate for meaningfully integrating local culture into the learning process. Therefore, instructional innovation is needed to combine local wisdom with a deep learning approach specifically, through